Sulyap sa lumipas : mga tahanang ansestral sa Kabite - Calairo, Emmanuel Franco. 4 0 16; 5 (Dasmariñas : Cavite Studies Center, De La Salle University, 1999)
Philippine ancestral houses in Cavite Province.
Includes bibliographical references (p. 119).
In Tagalog.
Keywords: 2 -- 0; 6; Architecture, Domestic;Dwellings -- Philippines;Cavite Province.;Philippines;Cavite Province. -- 20; 20; 2